A nationwide survey of psychological distress among Indonesian residents during the COVID-19 pandemic - Titik Respati; Siska Nia Irasanti; Dewi Sartika; Ieva Baniyah Akbar; Roy Rillera Marzo (Intelektual Pustaka Media Utama, 2021)
The Coronavirus disease (COVID-19) has become a public health emergency. The speed at which COVID-19 become pandemic and spread all over the world is alarming. A critical aspect of this type of pandemic is on the mental health of the community. This survey aimed to describe psychological distress in Indonesia's general population during the COVID-19 pandemic. Data collection began on 1st April 2020 to 30th April 2020. An online survey using Google Form with snowball sampling method used in this study. A modified version of the COVID-19 peri-traumatic distress index (CPDI) with 24 items used. The survey questionnaire included socio-economic and demographic variables. The study's total responses were 1,287, with 33 excluded from the analysis because of incomplete responses or not meeting inclusion criteria. Results showed that 63.5% of respondents reported having normal or no distress, 34% were having mild to moderate levels of distress, and 2.8% having severe distress. Age is the only variable that correlates with the level of distress. Healthcare workers and the general population showed no significant differences in the level of distress. During the early break of the COVID-19 pandemic, around 40% of respondents rated their psychological state having moderate to severe distress. These findings can be used to develop better psychological intervention measures and prevention of mental health during the pandemic.